Synthesis, DNA Binding, and Molecular Docking Studies of Dimethylaminobenzaldehyde-Based Bioactive Schiff Bases - Zainab M. Almarhoon; Wedad A. Al-Onazi; Asma A. Alothman; Amal M. Al-Mohaimeed; Eida S. Al-Farraj (Journal of Chemistry)
A new series of p-dimethylaminobenzaldehyde derivatives were tested for therapeutic potential by exploring their properties through characterization. The derivatives were synthesized by 1 : 1 condensation reaction of p-dimethylaminobenzaldehyde and substituted amines. The synthesized compounds 1–8 were characterized by different characterization techniques including IR, mass, 1H NMR, and 13C NMR spectroscopy, elemental analysis, and mass spectrometry. Furthermore, binding of these Schiff bases to Ct-DNA was examined by absorption spectroscopy, fluorescence quenching, circular dichroic, viscosity measurement, molecular docking, and molecular dynamics simulation methods. Schiff bases were tested for antimicrobial activity against bacterial species Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus by the disc diffusion method. The pharmacological treatment of Schiff bases showed that 1–8 have promising potential against tested bacterial strains. The molecular docking study of the target compounds was also carried out against B-DNA dodecamer d(CGCGAATTCGCG)2, and it has been found that 1–8 can bind to Ct-DNA via an intercalative mode. DPPH free radical and hydrogen peroxide scavenging assays were employed to assess the antioxidant potential of synthesized Schiff bases.